The Political Culture of Pesantren: Kyai's Authority in Jokowi's Victory in the 2019 Election East Java - Moh. Machrus Aly; Zainuddin; Jamilah (CV. Creative Tugu Pena, 2025)
This research examines in depth the role of kyai authority within Islamic boarding school culture as a determining factor in Joko Widodo's (Jokowi) victory in the 2019 Presidential Election in Jombang Regency. Using a qualitative approach relying on in-depth interviews with kyai, students, and community leaders, as well as a review of relevant documents, this study seeks to uncover how the charismatic influence of kyai shapes the political preferences of students and the community surrounding the pesantren. In the process, kyai employ religious framing mechanisms through regular religious studies and religious fatwas, which serve as effective tools for mobilizing political support. These mechanisms create emotional and ideological resonance that strengthens political loyalty among students and other pesantren communities. This research makes an important contribution to the theoretical discourse on the relationship between traditional religious authority and contemporary electoral dynamics in Indonesia, particularly in the context of local politics. The study also highlights the significant role of pesantren social networks in influencing election outcomes, as social spaces that are not only religious but also political. The research findings provide new insights into the transformation of the kyai's role, from initially being neutral in politics to becoming an active, strategic political actor in the context of local democracy. This demonstrates the adaptation of the role of the kyai to changing socio-political dynamics and illustrates the complexity of the interaction between religion and politics in Indonesia.